2020
DOI: 10.1186/s12870-020-02438-9
|View full text |Cite
|
Sign up to set email alerts
|

Transitions in wheat endosperm metabolism upon transcriptional induction of oil accumulation by oat endosperm WRINKLED1

Abstract: Background: Cereal grains, including wheat (Triticum aestivum L.), are major sources of food and feed, with wheat being dominant in temperate zones. These end uses exploit the storage reserves in the starchy endosperm of the grain, with starch being the major storage component in most cereal species. However, oats (Avena sativa L.) differs in that the starchy endosperm stores significant amounts of oil. Understanding the control of carbon allocation between groups of storage compounds, such as starch and oil, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 75 publications
0
25
0
Order By: Relevance
“…The presence of Ole-2 transcripts encoding the 16 kDa oleosin isoform suggests that these bodies are stabilised by oleosins as in most other oil-storing seed tissues. Although we have not directly demonstrated a role of oleosin in stabilizing lipid bodies in this paper, recent studies carried out in transgenic wheat support this suggestion: overexpression of the AsWRI1 transcription factor from oat in the starchy endosperm of wheat resulted in increases in accumulation of TAGs by up to nine-fold and in up-regulation of oleosin-encoding genes ( Grimberg et al, 2020 ). The fact that oleosins have not been reported in published proteomic studies of wheat starchy endosperm or white flour probably reflects technical problems, as oleosins are highly hydrophobic and not readily extracted in buffers used for proteomic studies.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…The presence of Ole-2 transcripts encoding the 16 kDa oleosin isoform suggests that these bodies are stabilised by oleosins as in most other oil-storing seed tissues. Although we have not directly demonstrated a role of oleosin in stabilizing lipid bodies in this paper, recent studies carried out in transgenic wheat support this suggestion: overexpression of the AsWRI1 transcription factor from oat in the starchy endosperm of wheat resulted in increases in accumulation of TAGs by up to nine-fold and in up-regulation of oleosin-encoding genes ( Grimberg et al, 2020 ). The fact that oleosins have not been reported in published proteomic studies of wheat starchy endosperm or white flour probably reflects technical problems, as oleosins are highly hydrophobic and not readily extracted in buffers used for proteomic studies.…”
Section: Resultsmentioning
confidence: 68%
“…However, the acyl-CoA independent pathway clearly also operates and the precise contributions of de novo DAG (Kennedy pathway) and PC-derived DAG remain to be determined. The importance of the Kennedy pathway is supported by the transcript analysis of wheat grains reported by Grimberg et al (2020) which also showed low levels of PDAT activity early in grain development and higher levels of DGAT/TAG1 activity.…”
Section: Resultsmentioning
confidence: 80%
“…In addition, synergy between RPBF and RISBZ1 has been implicated in mediating the regulatory networks essential for seed development by binding to the GCN4 motif to trans-activate the expression of seed storage proteins in rice [29,129]. Recently, Grimberg et al [130] identified an oat endosperm homolog of WRINKLED1 transcription factor (AsWRI1), which when expressed under the control of endosperm-specific HMW1Dx5 promoter, causes substantial alterations in carbon allocation in wheat grains, including lower seed weight and a wrinkled seed phenotype.…”
Section: Cereal Crop Traits Transcription Factor/gene Referencesmentioning
confidence: 99%
“…Many transcription factors (TFs) also participate in seed development and nutrient accumulation. TFs such as WRINKLED1 (WRI1), LEAFY COTYLEDON1/2 (LEC1/2), ABSCISIC ACID INSENSITIVE3 (ABI3), FUSCA3 (FUS3), PICKLE (PKL), and VP1/ABI3-LIKE (VAL) have been proved to regulate SOC in multiple species such as Arabidopsis, rapeseed, soybean, castor bean, and others [ 14 , 21 24 ].…”
Section: Introductionmentioning
confidence: 99%